Munchausen’s Syndrome Presenting as Hemoptysis in a 12-Year-Old Girl - Candice L Bjornson; Valerie G Kirk (Canadian Respiratory Journal)
The case of Munchausen’s syndrome presenting as hemop-tysis in a 12-year-old girl is presented. The features of Munchausen's syndrome are reviewed. Munchausen’s syndrome should be included in the differential diagnosis of hemoptysis in a child, especially when accompanied by a dramatic presentation, changing symptoms and negative diagnostic investigations.